2008
DOI: 10.1088/1742-5468/2008/10/p10020
|View full text |Cite
|
Sign up to set email alerts
|

Phase synchronization on scale-free and random networks in the presence of noise

Abstract: In this work we investigate the stability of synchronized states for the Kuramoto model on scale-free and random networks in the presence of white noise forcing. We show that for a fixed coupling constant, the robustness of the globally synchronized state against the noise is dependent on the noise intensity on both kinds of networks. At low noise intensities the random networks are more robust against losing the coherency but upon increasing the noise, at a specific noise strength the synchronization among th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…Besides the theoretical approaches described above, other aspects of the dynamics of the stochastic Kuramoto model were numerically addressed [283,[291][292][293][294][295]. In particular, Traxl et al [283] developed a numerical framework and systematically analyzed the influence of noise and coupling strength on the maximum degree of synchronization of several networks; including fully connected, random, modular and real topologies.…”
Section: Gaussian Approximationmentioning
confidence: 99%
“…Besides the theoretical approaches described above, other aspects of the dynamics of the stochastic Kuramoto model were numerically addressed [283,[291][292][293][294][295]. In particular, Traxl et al [283] developed a numerical framework and systematically analyzed the influence of noise and coupling strength on the maximum degree of synchronization of several networks; including fully connected, random, modular and real topologies.…”
Section: Gaussian Approximationmentioning
confidence: 99%
“…In our numerical work, we choose a box distribution in the interval [−w/2, w/2] for η, so that its variance is equal to D = w 2 /24. It can be shown that by proper re-scaling of the time variable, the effect of parameters D and K can be included in a single parameter g 2 = D K [15], converting the dynamical equations to:…”
Section: The Effect Of Random Forcementioning
confidence: 99%
“…One of such models has been proposed by Kuramoto, which consists of a set of oscillators with fixed amplitude (phase oscillators) mutually coupled by a 2π periodic interaction [13]. The stochastic Kuramoto model has been studied on the globally connected [14] networks [15]. Analytical results on an all-to-all network show that for a given distribution of intrinsic frequencies of oscillators, a minimum value of coupling is needed for synchronization.…”
Section: Introductionmentioning
confidence: 99%
“…, P t (τ )) T , which evolves according to P t+1 = F ( P t ). Note that F 1 is the only component of F which is nonlinear [see (13)]. From (9), the fixed point for any 2 ≤ s ≤ τ −1 is clearly P * s ≡ P ∞ (s) = P ∞ (s−1) = · · · = P * 1 which, upon substitution in (10), gives P * τ = P * 1 /p γ .…”
Section: Mean-field Analysismentioning
confidence: 99%